Español - Jaramillo-Mediavilla, Lorena; Mediavilla-Sarmiento, Ana-Lucía (Revista Ecos de la Academia, 2021)
Digital transformation is a process to which society has had to adapt because it was not an option but a necessity. This implies that, while it is being articulated and taking root in any context, it requires a change in culture, in mentality supported by new technologies that optimize resources, transcend and achieve geographical scope that, without these, years ago was not possible. This investigation took place in the quarter from April to June 2020 where the COVID 19 pandemic was on the rise, a decisive moment to promote those who were already in this transformation and in other cases forced to evolve. The Institutions of Higher Education (IES) for their condition of offering knowledge and being the academy, who are the object of study of this research, allowed to demonstrate the objective that was pursued since after the analysis of the work carried out in their fan pages and interviews with Authorities in charge of these in the Imbabura universities were fundamental to define a proposal for the professional profile of a Community Manager who works in an HEI and it was shown that they have Community Managers (CM), directed and committed to the mission of each of they.